Enhancement of aging rat laryngeal muscles with endogenous growth factor treatment - Stemple, Joseph C. (Physiol Rep, 2016)
Clinical evidence suggests that laryngeal muscle dysfunction is associated with human aging. Studies in animal models have reported morphological changes consistent with denervation in laryngeal muscles with age. Life‐long laryngeal muscle activity relies on cytoskeletal integrity and nerve–muscle communication at the neuromuscular junction (NMJ). It is thought that neurotrophins enhance neuromuscular transmission by increasing neurotransmitter release. We hypothesized that treatment with neurotrophin 4 (NTF4) would modify the morphology and functional innervation of aging rat laryngeal muscles. Fifty‐six Fischer 344xBrown Norway rats (6‐ and 30‐mo age groups) were used to evaluate to determine if NTF4, given systemically (n = 32) or directly (n = 24), would improve the morphology and functional innervation of aging rat thyroarytenoid muscles. Results demonstrate the ability of rat laryngeal muscles to remodel in response to neurotrophin application. Changes were demonstrated in fiber size, glycolytic capacity, mitochondrial, tyrosine kinase receptors (Trk), NMJ content, and denervation in aging rat thyroarytenoid muscles. This study suggests that growth factors may have therapeutic potential to ameliorate aging‐related laryngeal muscle dysfunction.